Comparison Between Noninvasive and Invasive Blood Pressure Monitoring in Post Percutaneous Coronary Intervention Patients Admitted to Cardiac Intensive Care Unit - Ngabea, Murtala, Audu (International Journal of Innovative Research in Medical Science, 2023)
Background: Percutaneous coronary intervention (PCI) remains one of the most important treatment modality for all the spectrum of artherosclerotic coronary artery disease. Post PCI patients are routinely admitted into the cardiac intensive care unit (ICCU) for observation and further management during which blood pressure (BP) and other hemodynamic parameters are monitored. Blood pressure (BP) monitoring is vital for the management of hemodynamically unstable patients in the cardiac intensive care Unit (ICCU). Despite errors from inaccurate calibration, movement artifacts and over or underdamping, invasive arterial blood pressure (IABP) monitoring remains the preferred method of monitoring BP in hemodynamically unstable patients. Nonetheless, automated noninvasive BP (NIBP) monitoring is commonly used in critically ill patients in cardiac ICU. Aim of study: To compare IABP using radial and femoral arterial line with NIBP monitoring, and to determine if radial and femoral arterial lines can be used interchangeably in patients undergoing PCI. Methodology: A total of eighty post PCI patients who had arterial line cannulation during PCI and admitted into ICCU were enrolled. Study participants were divided into two groups of Fourty (40) patients each. One group had IABP monitoring via right femoral artery line while the second group had IABP monitoring via right radial artery cannular. A cuff was placed on the left arm for concurrent noninvasive BP monitoring in all 80 patients. Data were obtained by performing noninvasive blood pressure (NIBP) t and concurrent IABP four times at one hourly intervals with first reading taken at time of admission to cardiac intensive care unit labelled (T1). NIBP values were compared with IABP values as the reference standard. Results: There were significant differences between systolic IABP as well as mean arterial invasive blood pressure measurements obtained through both radial and femoral routes compared with noninvasive blood pressure measurements (NIBP). No statistically significant differences in invasive blood pressure measurements between the radial and femoral catheter routes was detected. Conclusion: Noninvasive blood pressure measurement alone is insufficient for monitoring of post PCI patients admitted to cardiac intensive care unit after coronary angioplasty. The femoral and radial arterial lines can be used interchangeably for blood pressure monitoring in cardiac intensive care unit.